Building flux capacity: Citizen scientists increase resolution of soil greenhouse gas fluxes. - Cody C Reed; Julianne M Winters; Stephen C Hart; Rachel Hutchinson; Mark Chandler; Gitte Venicx; Benjamin W Sullivan (PLoS ONE)
Though citizen science programs have been broadly successful in diverse scientific fields, their adoption has lagged in some disciplines, including soil science and ecosystem ecology. Collaborations with citizen scientists may be viewed as a conundrum in these disciplines, which often require substantial labor and technical experience; citizen scientists could improve sampling capacity but may reduce sample quality or require training and oversight prior to and while performing specialized tasks. To demonstrate the feasibility of incorporating citizen scientists into soil biogeochemistry research, we conducted a proof-of-concept study in high-elevation meadows of the Sierra Nevada in California. A collaboration between university researchers and citizen scientists allowed us to assess spatial and diel patterns of soil greenhouse gas (GHG) fluxes with an intensity and frequency that would otherwise be beyond the capacity of a typical research laboratory. This collaboration with citizen scientists increased our sampling intensity by over 700% while only doubling the sampling error relative to that of full-time researchers. With training and support from project scientists, citizen scientists collected data that demonstrate spatial independence of carbon dioxide, methane, and nitrous oxide at scales between 1 m and 175 m. Additionally, we found a lack of temporal variation over a 24-h period for all three GHGs. Citizen scientists participating in this one-day event reported levels of satisfaction commensurate with longer-term, immersive campaigns. The place-based event also proved an effective tool for teaching intangible concepts of soil biogeochemistry and promoting local conservation. Despite perceived barriers to entry, this study demonstrates the mutual benefits of citizen science collaborations in soil science and ecosystem ecology, encouraging adoption by disciplines that have been slow to take advantage of such collaborations. Short-term, local citizen science events can provide meaningful experiences for area residents and teach global biogeochemical cycles in a place-based context.